Student And E–Assessment Authentication In Distance Learning - Mugambi, K.D.; Sansa-Otim, J.; Bulega, T. (RUFORUM, 2016)
Distance learning has grown from the use of print media and video tapes to campus portal access and internet based access to online resources in order to take advantage of electronic benefits. Although online courses provide access to higher education through distance learning systems, they pose challenges for academic integrity. Paramount to this is contract cheating where duly registered students contracts out their coursework to writers in order to submit the purchased assignments as their own work and impersonation where a duly registered student passes his/her security information to a fraudulent, who uses it to answer the exam. Therefore, it becomes a challenge to verify the identity of a distance learner or the writer of the long distance learner assignment. To detect and verify such form of cheating, we propose a student verification model that comprises of two methods, keystroke dynamics and stylometrics analysis.The student verification model expected outcome is measurement of accuracy in authenticating students and e-assessments in distance learning.
Keywords: Contract cheating, distance learning, e-assessments, keystroke dynamics, impersonation, stylometrics